Bacterial flavin-containing monooxygenase is trimethylamine monooxygenase - Chen, Yin (National Academy of Sciences, 2011)
Flavin-containing monooxygenases (FMOs) are one of the most important monooxygenase systems in Eukaryotes and have many important physiological functions. FMOs have also been found in bacteria; however, their physiological function is not known. Here, we report the identification and characterization of trimethylamine (TMA) monooxygenase, termed Tmm, from Methylocella silvestris, using a combination of proteomic, biochemical, and genetic approaches. This bacterial FMO contains the FMO sequence motif (FXGXXXHXXXF/Y) and typical flavin adenine dinucleotide and nicotinamide adenine dinucleotide phosphate-binding domains. The enzyme was highly expressed in TMA-grown M. silvestris and absent during growth on methanol. The gene, tmm, was expressed in Escherichia coli, and the purified recombinant protein had high Tmm activity. Mutagenesis of this gene abolished the ability of M. silvestris to grow on TMA as a sole carbon and energy source. Close homologs of tmm occur in many Alphaproteobacteria, in particular Rhodobacteraceae (marine Roseobacter clade, MRC) and the marine SAR11 clade (Pelagibacter ubique). We show that the ability of MRC to use TMA as a sole carbon and/or nitrogen source is directly linked to the presence of tmm in the genomes, and purified Tmm of MRC and SAR11 from recombinant E. coli showed Tmm activities. The tmm gene is highly abundant in the metagenomes of the Global Ocean Sampling expedition, and we estimate that 20% of the bacteria in the surface ocean contain tmm. Taken together, our results suggest that Tmm, a bacterial FMO, plays an important yet overlooked role in the global carbon and nitrogen cycles.